Evaluation of The Use of Wordwall Application in The Learning of Indonesian at SMA N 1 Polanharjo - Listianingsih, Putri; Sulistyono, Yunus (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The purpose of this study is to describe the evaluation of the use of the Wordwall game application in learning Indonesian at SMA N 1 Polanharjo, to identify the obstacles faced by students in implementing the Wordwall game, and to identify the advantages and disadvantages of utilizing the Wordwall game application for learning Indonesian. Evaluation in this context can be in the form of educational games that are tailored to students' needs. Methodology: This study used a qualitative descriptive method. Data were collected through several techniques, namely observation, interviews, and documentation. The data analysis process was carried out in three stages: data reduction, data display, and conclusion drawing. The object of this study was the students of SMA N 1 Polanharjo. Primary data were obtained from direct observations of the students, while secondary data consisted of scientific writings or previous research on the use of the Wordwall.net educational game as a reference for this study. Results: The results of the study show that the use of Wordwall in learning evaluation brings significant improvements in various aspects. There is a rapid increase in students' enthusiasm during the evaluation process, a noticeable improvement in their concentration, and enhanced cooperation among individuals. The study concludes that Wordwall media can support students’ abilities and increase their motivation. The application of Wordwall media strongly supports the activeness of learning activities, improves the effectiveness of learning, and makes students more enthusiastic in participating in lessons. Applications/Originality/Value: The application of this research lies in its contribution to the implementation of game-based learning evaluation tools, specifically the Wordwall application, in secondary education. The study demonstrates that integrating Wordwall into Indonesian language learning can enhance student motivation, concentration, and collaboration. These findings suggest that educators can adopt Wordwall not only as an evaluation tool but also as a learning strategy to increase student engagement and participation. The study also provides practical insights into the obstacles students may face, offering a foundation for further development and adaptation of digital media in classroom settings to optimize learning effectiveness.